Adaptive information provisioning in an agent-based virtual organization-ontologies in the system - Szymczak, M.; Frackowiak, G.; Gawinecki, M.; Ganzha, M.; Paprzycki, M.; Park, M.-W. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2008)
In this paper we consider utilization of ontologies in an agent-based virtual organization. Specifically, in the system flexible delivery of information is to be based on matching of ontologically demarcated resource profiles, work context(s), and domain specific knowledge. In this paper we introduce basic ontologies and their applications. ？ 2008 Springer-Verlag Berlin Heidelberg.